Between Theory and Practice: The Possibility of a Right to Free Speech in the People’s Republic of China - Lin, Peter (Columbia Journal of Asian Law, 1990)
Scholars often struggle to understand why the People’s Republic of China (PRC) has not developed the kind of democratic rights and institutions prevalent in the West. One traditional explanation is that Western conceptions of democratic rights and Chinese socialist values are separated by an unbridgeable gap. It is thought that the Chinese people, steeped in Confucian values for centuries and now recently immersed in socialism, simply have no desire to pursue the ideals advanced in Western rights discourses. Hua Sheng’s foregoing retro- spective, Big Character Posters in the PRC.: A Historical Survey (His- torical Survey), poses a potent challenge to this view.’ Historical Survey does not portray a complacent people quietly accepting the dictates of what Confucius would call a “virtuous ruler,” but a people struggling relentlessly for freedom of thought, belief, and speech against a repressive government. Reflecting on this history, the present essay explores how a right to freedom of speech in general, and a right to write big character posters (dazibao) in particular, can be realized in the PRC. Drawing on the insights generated by contemporary legal theories, it advances a rights theory to provide a theoretical basis for the development of rights and democratic institutions in the PRC. This essay begins with a critical examination of the theoretical explanations for the source of democratic rights and institutions traditionally provided by the “nat- ural rights theory.” It argues that the natural rights theory constructs a sharp yet fictive distinction between “liberal individualism” and “socialist collectivism.” Consequently, the natural rights theory is unable to explain why rights and freedoms exist in the West, but are generally absent in the PRC.